Preliminary study on the use of washed rice water as a natural fertilizer for germination and growth of water spinach - Abdullah, Siti Nur Azmu’i; Rodzali, Nur Nadirah; Haznee, Batrisyia Izzati; Hasmirah, Nik Aqilah; Aziz, Nur Alia Aqilah; Zamri, Nur Ayu Syafiqah; Zulsafari, Nur Nisha Maisara; Wan Shah Rizal, Wan Syazriena Ridzwin (2025)
Washed rice water (WRW), the starchy liquid left after washing rice, is rich in essential nutrients such as nitrogen, phosphorus, potassium, and beneficial microbes. This study evaluates the effectiveness of WRW as a sustainable and eco-friendly alternative to chemical fertilizers in promoting seed germination and early plant development. Water spinach (Ipomoea aquatica) seeds were pre-soaked and planted in black soil, with three treatment groups; tap water (control), fresh rice water, and aged (three days) rice water. Each treatment was replicated, and plants were watered every two days over 30 days. Growth parameters including germination rate, plant height, and number of leaves were measured. The results show that aged rice water achieved a 90% germination rate, along with the greatest leaf production and plant height, compared to fresh rice water and the control. This suggests that aged rice water could serve as an affordable and sustainable substitute for synthetic fertilizers, making it particularly advantageous for small-scale farmers and home gardeners. The study contributes to sustainable agricultural practices by promoting WRW as a low-cost, environmentally friendly fertilizer for improving crop yields and plant health.